Relación entre la inteligencia emocional y bienestar psicológico en adolescentes de dos escuelas públicas de Lima Metropolitana - Mendiola Arrisueño, Cristina (2019)
The purpose of this research was to determine the relationship between emotional intelligence and psychological well-being in adolescents between the ages of 13 and 17 who are between third and fifth year of high school in two public schools in Metropolitan Lima. The sample consisted of 177 students who attend between third and fifth on average. These were selected through a non-probabilistic sample. To measure the study variables, the Baron Emotional Intelligence Inventory and the Psychological Wellbeing Scale for Young BIEPS-J were applied. It was obtained as a result that there is a statistically significant relationship (rs = .38, p <.001) between Emotional intelligence and psychological well-being. This indicates the importance of developing emotional, personal and interpersonal skills from an early age that relate to our general ability to meet the demands of the environment, which is related to the person's perception of their achievements, the degree of satisfaction with what he has done, does or can do, that leads to rich their true potential (Casullo et al., 2002).